2017
DOI: 10.4172/2472-1077.1000113
|View full text |Cite
|
Sign up to set email alerts
|

Infections and Childhood Psychiatric Disorders: Tick-Borne Illness and Bipolar Disorder in Youth

Abstract: Objective: To explore possible links between tick-borne illness (TBI) and pediatric bipolar disorder (PBD) in a retrospective series of youth from a Northeast U.S. psychiatric private practice.Methods: PBD diagnosis in 27 youth (15 Bipolar I and 12 Bipolar II) was based on DSM-IV TR criteria following interviews with parents and children, questionnaires and school reports. Testing for Borrelia burgdorferi (Lyme disease), Babesia, Bartonella, Mycoplasma pneumoniae, Anaplasma and Ehrlichia occurred between Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…infection may play a role in some cases of pediatric mood disorders. 19 Consistent with these observations, all three patients in this study initially saw mental health professionals due to the psychiatric/ psychological nature of the presenting symptoms. Mood disturbances, heightened anxiety, difficulty with school attendance and academic performance were the overwhelming clinical manifestations in each case.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…infection may play a role in some cases of pediatric mood disorders. 19 Consistent with these observations, all three patients in this study initially saw mental health professionals due to the psychiatric/ psychological nature of the presenting symptoms. Mood disturbances, heightened anxiety, difficulty with school attendance and academic performance were the overwhelming clinical manifestations in each case.…”
Section: Discussionsupporting
confidence: 78%
“…These include resistance to complement activation, antigenic variation of surface proteins, and inhibition of host cell apoptosis. 19 There are no gold-standard diagnostic tests to confirm Bartonella spp. infection.…”
mentioning
confidence: 99%
“…An outpatient retrospective chart review without a control group demonstrated 80% of children with psychiatric illness referred to a child psychiatrist, 49 of the 69 without a known history of LB or other TBD, demonstrated evidence of exposure to one or more of the pathogens B. burgdorferi , Bartonella, Babesia , Ehrlichia and Anaplasma on serologic testing performed by multiple laboratories and 22% of children with an onset of bipolar disorder referred to a child psychiatrist tested CDC surveillance criteria positive for LB. In addition, 74% of these children tested positive to exposure to one or more of the pathogens B. burgdorferi , Bartonella, Babesia , Ehrlichia and Anaplasma on serologic testing performed by multiple laboratories [ 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Bipolar disorder has been associated with a number of infections including LB [ 46 , 73 , 80 , 81 , 82 ]. When bipolar disorder is seen in LB patients, it is invariably rapid cycling [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…When bipolar disorder is seen, it is invariably rapid cycling [12]. The prevalence of bipolar illness in LB/TBD is 74% (in children) [75], 47% (mood swings) [76], 28% (homicidal) and 10% [12]. Depression Depression from LB/TBD can frequently be prevented with early diagnosis and effective treatment [77].…”
Section: Developmental Disordersmentioning
confidence: 99%